Gender-specific stress tolerance variations in academic volleyball - Shilko, V. G.; Potovskaya, E. S.; Shilko, T. A.; Krupitskaya, O. N. (Theory and Practice of Physical Culture, 2017)
The article presents findings of a sociological survey of the gender-specific variations of stress tolerance in academic volleyball. Both male and female respondents were requested to rate on a 5-point scale stress levels of different problems they have faced for three academic years. The survey data and analysis made it possible to rate the gender-specific variations of stress tolerance versus the physical education and sport activity for a number of stressors hampering the subjects` social and psychological adaptation to the academic environment.